The Central Council for the Care of Cripples : What it is, and what it does
1933-12 1933 1930s 4 pages CONSTITUTION OF COUNCIL. The Central Council consists of representatives of Local Associations for the Care of Cripples and other organisations dealing with cripples, including nearly all the orthopaedic hospitals. It also includes amongst its members the leading orthopaedic surgeons, and representatives of national organisations such as the British Red Cross Society, the Invalid Children's Aid Association, etc. The Council is, therefore, in fact a federation of all persons and bodies working for cripples. The Central Council is recognised by Government Departments concerned as the only authoritative body dealing with the cripple problem as a whole throughout the United Kingdom. PREVENTION IS BETTER THAN CURE. There will always be a certain number who have become permanently disabled by accident, or who have been born with incurable deformities. But it is estimated that 80% of the present cripple population need never have become crippled if they had received proper treatment in childhood. Most cripples have become so owing to neglect of such diseases as infantile paralysis, rickets and tuberculosis. Prompt and efficient treatment can cure these diseases. It can also remedy most congenital deformities and cure or alleviate the results of most accidents. There is no reason why most potential cripples, instead of becoming a burden on the community, should not grow up into healthy and self-supporting citizens. And yet some 10,000 children are still becoming crippled every year. WHAT IS NEEDED? To cure children suffering from crippling diseases, to remedy congenital deformities, and to treat all those (adults as well as children) who have become crippled from any cause, there is an urgent need for more hospitals specialising 292/841.51/2/4